2021
DOI: 10.1002/ejhf.2202
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical experience with cardiac contractility modulation therapy delivered by the Optimizer Smart system

Abstract: We assessed long-term effects of cardiac contractility modulation delivered by the Optimizer Smart system on quality of life, left ventricular ejection fraction (LVEF), mortality and heart failure and cardiovascular hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 13 publications
(26 reference statements)
2
31
0
11
Order By: Relevance
“…Recent results from the largest published registry to date, CCM-REG25-45, showed that the survival rates of patients with LVEF <35% were significantly higher than the survival predicted by the SHFM ( p = 0.46) ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent results from the largest published registry to date, CCM-REG25-45, showed that the survival rates of patients with LVEF <35% were significantly higher than the survival predicted by the SHFM ( p = 0.46) ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two mechanisms justify the improvement in cardiac contractility (in the absence of increased myocardial oxygen consumption) that CCM therapy should be used for patients with HFrEF [ 10 ]. CCM therapy was associated with improvements in exercise tolerance (both the distance covered in the 6-min walking distance test and the VO 2 peak in the cardiopulmonary exercise test), an increase in quality of life, a reduction in HF hospitalizations, and reverse remodelling of the left ventricle (reduction in left ventricular volumes and increase in LVEF) [ 5 , 11 , 12 ]. The current guidelines on the diagnosis and management of acute and chronic heart failure by the European Society of Cardiology [ 3 ] state that CCM should be considered in patients with HF, NYHA class III–IV HFs, an LVEF ≥25% to ≤45%, and a QRS duration <130 ms.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was treated with intravenous diuretics and levosimendan and achieved a euvolemia state after three days of admission with a reduction in NT-proBNP to 976.8 pg/mL. According to ESC guidelines on the management of chronic and acute HF and the results of DANISH trials [5], given the low risk of arrhythmic sudden cardiac death of the patient, we did not opt for ICD implantation; instead, to reduce HF-related hospitalizations and to improve quality of life, The NT-proBNP value was 1305.4 pg/mL, and the Minnesota Living with Heart Failure Questionnaire (MLHFQ) score was 82 points. The patient was treated with intravenous diuretics and levosimendan and achieved a euvolemia state after three days of admission with a reduction in NT-proBNP to 976.8 pg/mL.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations